Formação inicial de professoras e professores para a Educação Infantil: o Curso de Pedagogia em foco - Craveiro, Thábata Saunders Uchôa (2025)
This dissertation investigated the initial training of teachers for early childhood education, a stage of Basic Education that requires specific knowledge, skills, and values. The research problem sought to understand how the Pedagogy course at the Faculty of Education of the Federal University of Ceará (FACED/UFC) has contemplated this training in its curriculum. The relevance of the study lies in the need to understand the formative gaps and the challenges faced by teacher educators and students in the training process, contributing to the construction of ethical, aesthetic, situated, and qualified paths in preparation for teaching in early childhood education. The general objective was to analyze how the Political-Pedagogical Project of the Pedagogy course at UFC, both day and evening programs, addressed the training for teaching in early childhood education. The specific objectives involved: identifying how the curriculum matrix, the subjects, and the supervised internship component address this training; understanding the conceptions, evaluations, and expectations of the early childhood education faculty; and apprehending the perceptions of graduates regarding their preparation for teaching in nurseries and preschools. The analysis was based on authors who discuss the history and identity of the Pedagogy course in Brazil, models of teacher education, the specificities of early childhood education, and teaching professionalism, with emphasis on Saviani (2009, 2021), Silva (1999), Giseli B. Cruz (2008), Formosinho (2009), Oliveira-Formosinho (2005, 2009), Kramer (1994, 2005), Cruz (2000, 2008, 2023), and Sarmento (2004). This qualitative research was configured as an intrinsic case study. The procedures included the analysis of the Pedagogical Project of the Course and the conduction of semi-structured interviews with faculty members in the area and with graduates working in early childhood education. The results reveal that, although the FACED/UFC curriculum has advanced in including components focused on the area, a generalist, academicist logic persists, with limited articulation between theory and practice and a low workload allocated to early childhood education, especially teaching with infants and toddlers. The supervised internship is recognized as central to the articulation of theory and practice and to the construction of teaching identity, being understood as a space for experimentation and reflection. However, it is perceived as insufficient and concentrated at the end of the course. The graduates pointed out gaps in their preparation for the daily challenges of practice, especially in contexts of social vulnerability, as well as in addressing ethnic-racial relations, special education, and the relationship with families. Meanwhile, the faculty highlighted the absence of institutional permanence policies and the symbolic marginalization of early childhood education in the academic environment. The research reinforces the need for a more integrated curriculum that expands the time and space dedicated to early childhood education in teacher training and considers the students' concrete living conditions.